Ecopreneur: Bridging the gap between conventional teaching and learner achievement - Arumugam, Nalini; Bala Subramaniam, Asha Latha; Selvanayagam, Sivajothy; Manap, Mohammad Radzi; Md Razak, Mohamad Idham; Bakri, Mohammed Hariri (Horizon Research Publishing, 2020)
In 21st century education, it is imperative for educators to exploit technology in order to meet the evolving education needs of the current generation through greater access to knowledge. The researchers cum educators supplemented the conventional-based classrooms teaching of entrepreneur education with a customized home-based and interactive e-learning platform, ECOPRENEUR, to increase learner participation, engagement and achievement. The research employed a mixed method approach to elicit data from 385 undergraduates from an established public university in Malaysia to determine the efficacy of the e-learning platform as a supplementary learning tool in the teaching of Technology Entrepreneurship. Findings reveal that the intervention supplementary learning platform improves students’ overall grades in Technology Entrepreneurship: m = 44.04 in the pre-test and m= 53.63 in the post-test. Paired sample test results demonstrate a statistically significant grade outcome (t = 28.679; n=385; p=.000). Further findings reveal that the male students in the study secured higher grades with a mean of 55.72 compared to female students with a mean of 52.26 (p=.000) in the post-test. Both pre and post-test scores show that students from the Faculty of Computer Science and Mathematics outperformed (pre-test mean with 45.76 and post-test 56.69) students from the Faculty of Plantation and Agro Technology (pre-test m=42.29 and post-test m= 50.51), thus indicating that motivation and expertise in information and communication technology to navigate the platform play a major role in determining its efficacy.